PENGARUH PEMBERIAN TERAPI SEFT DAN MENDENGARKAN BACAAN AL-QUR’AN TERHADAP NYERI PASIEN POST OPERASI HERNIA - Alvin Abdillah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Hernia postoperative pain is the sensation of pain felt by the patient's postoperative irritation caused by thestimulation of peripheral nerves along due to surgery. Fromthe results of the preliminary study in ward Irna A HospitalSyarifah Ambami Rato Ebu Bangkalan, it is found that thehigh incidence pain of postoperative hernia. The purpose ofthis study is to determine the effect before and after therapySEFT and listen Qur'an in patients with postoperativehernia in Irna ward A Hospital Syarifah Ambami Rato EbuBangkalan. The study design used "pre-experimental" approachwith one-group pre-post test design. Population estimates istaken 15 respondents and the samples were taken by 13respondents. Sampling technique was using a quotasampling independent variables of Research is therapeuticSEFT and listen Qur'an and the dependent variable ofresearch was pain of postoperative hernia. While the datacollection tool used observation sheets with numerical scaleof 0-10 with Wilcoxon statistical tests. The results showed that pain of postoperative herniaon the respondent before therapy was given SEFT andlistening reading the Qur'an 8 (61.5%) of respondents with amean of 3.08 experiencing severe pain, while the therapywas given after SEFT theraphy and listening to reading AlQur'an 6 ( 46.1%) of respondents with a mean of 1.23experiencing mild pain. Based on the results statisticallyusing the Wilcoxon, showed P Value: 0,002 <α: 0.05, whichmeans there were significant pain of postoperative herniabefore and after given therapy listening to the recitation ofAl-Qur'an.Based on the above results, that therapeutic SEFT and listen Qur'an is very effective in lowering pain of postoperativehernia. So when experiencing pain of postoperative hernia,respondents are expected to use the therapy SEFT andreading Al-Qur'an as a non-pharmacological solutions.